Determinants of Sovereign Risk: Macroeconomic Fundamentals and the Pricing of Sovereign Debt - Hilscher, Jens; Nosbusch, Yves (Review of Finance, 2010)
This paper investigates the effects of macroeconomic fundamentals on emerging market sovereign credit spreads. We find that the volatility of terms of trade in particular has a statistically and economically significant effect on spreads. This is robust to instrumenting terms of trade with a country-specific commodity price index. Our measures of country fundamentals have substantial explanatory power, even controlling for global factors and credit ratings. We also estimate default probabilities in a hazard model and find that model implied spreads capture a significant part of the variation in observed spreads out-of-sample. The fit is better for lower credit quality borrowers.